General Anesthesia Management of Super Refractory Status Epilepticus in Anti-N-Methyl-D-Aspartate-Receptor (NMDAR) Meningitis - Amalia, Putri Shabrina; Setiawan, Irvan; Melati, Annemarie Chrysantia (International Journal of Integrated Health Sciences, 2025)
Background: Super Refractory Status Epilepticus poses significant management challenges, requiring intensive therapeutic approaches including general anesthesia.Objective: To discuss the management of Super Refractory Status Epilepticus (SRSE) with general anesthesia to control seizures.Case Illustration: A 17-year-old female with tonic-clonic seizures, headache, unclear speech, and a change in behavior, who also appeared to be restless, was presented. She was admitted to the intensive care unit and administered anticonvulsant medication. A brain MRI with contrast showed the impression of meningitis, and cerebrospinal fluid examination showed a positive anti-NMDAR result. First-line therapy involved high-dose steroids and intravenous immunoglobulin for 5 days, followed by second-line therapy with rituximab. Patient received general anesthesia using sevoflurane volatile, dexmedetomidine, continuous rocuronium, propofol, ketamine, and fentanyl due to persistent seizures despite receiving anticonvulsant therapy. Monitoring was conducted for vital signs, seizure activity, and depth of anesthesia using the bispectral index (BIS). Tonic-clonic seizures in patients were successfully managed with general anesthesia. However, facial dyskinesia was still present despite the administration of general anesthesia. Facial dyskinesia worsened upon discontinuation of continuous rocuronium.Conclusion: General anesthesia could be used in the management of SRSE with the aim of controlling seizures and preventing complications arising from continuous seizures.